The analysis of grammatical shifts in translating English news into Arabic / Nael F. M. Hijjo - Nael, F. M. Hijjo (2013)
The challenging issues with reference to grammatical shift as one aspect for an adequate translation have been widely studied. However, the present study investigates the grammatical shifts issues within media translation settings. Since “most readers are probably unaware of the role played by translation in international news reporting” (Schäffner and Bassnett, 2010), accordingly, this study attempts to determine the types of the grammatical shifts between English as a source language (SL) and Arabic as a target language (TL) that are realized when translating English media news into Arabic. Furthermore, it examines the quality of the source text message after applying the grammatical shifts. To attain the research objectives, Catford’s notion on Translation Shifts (1965) is employed. The research corpus is a raw data that consists of 40 English written news texts and their Arabic correspondences which are collected from British Broadcasting Corporation (BBC) channel website. The findings show that optional and obligatory shifts have been applied. It also finds that BBC translators applied all types of shifts in translation from English to Arabic. Translators of BBC news from English into Arabic applied all types of shift to preserve the meaning of the source text and to sustain its quality of the message. Yet, the findings suggest that BBC translators failed to sustain the meaning and the quality of the message when they applied structural shifts of sentence structure from passive voice to active voice and in some cases of unit-shifts. Keywords: grammatical shifts, translation, media news, English, Arabic.